PENGASUHAN DAN KEADAAN GIZI ANAK DARI IBU YANG BEKERJA DI DKI JAKARTA - Heryudarini Harahap; Dyah Santi Puspitasari (Persagi, 1992)
PENGASUHAN DAN KEADAAN GIZI ANAK DARI IBU YANG BEKERJA DI DKI JAKARTA